PERBANDINGAN PEMBERHENTIAN PRESIDEN DALAM MASA JABATAN DI INDONESIA DAN BRASIL: Comparison of Presidential Terminations in Terms Occupations in Indonesian and Brazil - Pratama, Farhan Tulus; Wijiningsih, Ninuk (AMICUS CURIAE, 2024)
The president is the head of government and head of state in Indonesia and Brazil. During the course of their administration, there are dynamics that each president in both countries experiences, and some have even been forced to resign before the end of their term. Both countries have their own mechanisms for removing a president from office, which leads to the research question: How similar and different are the processes for removing a president in Indonesia and Brazil? Additionally, were the procedures followed in accordance with the relevant laws and regulations during the president's term in both countries? This study uses a comparative normative method with a descriptive nature. Secondary data used in this study include legislation, journals and related books, as well as the Kamus Besar Bahasa Indonesia (Indonesian language dictionary) and legal dictionaries. The researcher drew several conclusions from this study: (1) The mechanisms for removing a president in Indonesia and Brazil have similarities and differences. (2) There is consistency in the removal of President Abdurrahman Wahid and Ir. Soekarno, but inconsistency in the case of Fernando.